The future of complement therapeutics - Kolev, Martin; Rao, Kollu Nageswara; Yeh, Michael; Parikh, Atman; Deschatelets, Pascal (Exploration of immunology, 2024)
Complement is both evolutionary and scientifically old. It predates the adaptive immunity by some 600 million years and was first described in 1905 by Jules Bordet and Paul Ehrlich. For the most of its, the existence complement system has been ignored by most scientists and clinicians due to the perception of it being complicated and its relevance for the pathogenesis of human disease being unclear. With the recent US Food and Drug Administration (FDA) approvals of pegcetacoplan for both paroxysmal nocturnal haemoglobinuria (PNH) and geographic atrophy (GA), avacincaptad pegol for GA and iptacopan and danicopan for PNH, we are at a crucial juncture for complement-targeting therapies. A number of companies and academic institutions are developing next-generation complement therapies, which is resulting in an increasingly competitive landscape. If one looks at the serum complement cascade, all 3 pathways now have biotechnology or pharmaceutical industry players with 1 or multiple clinical-stage inhibitors that are expected to be FDA approved within the next few years. Furthermore, with the limited number of clinically validated targets in complement-mediated disease, the competition in this space is set to further intensify in the coming years. In this review, we will discuss the timeline of the academic discoveries that led to the development of the current crop of FDA-approved complement therapeutics. We follow with a discussion of an increasingly crowded complement therapy space and of the scientific advances that have emerged in recent two decades underpinning future innovation, including advances in our understanding of complement biology, such as local and intracellular complement, emerging complement targets, combinational approaches of complement and non-complement therapeutics to unlock new disease indications and new technologies such as gene therapy. We will also give a comprehensive overview of the gene therapy landscape and how it can be utilized to target complement dysregulation.